2018
DOI: 10.1097/md.0000000000010186
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa associated with systemic lupus erythematosus

Abstract: Rationale:Hidradenitis suppurativa (HS) is a chronic inflammatory condition characterized by recurrent swollen, deep, and painful abscesses. Several autoimmune conditions have been shown to be associated with HS including inflammatory bowel disease and spondyloarthropathies.Patient concerns:40-year-old female with systemic lupus erythematous (SLE) presented with recurrent abscesses and nodules on her extremities.Diagnosis:Early considerations related the described dermatologic findings to the dermatologic mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Interestingly, other rheumatologic conditions have been reported in patients with HS, such as systemic lupus erythematous. In a 2018 case report (Ben David et al, 2018), a 40-year-old female patient with SLE presented with recurrent abscesses and nodules on the extremities and was ultimately diagnosed with HS. Thus, HS may coexist with other autoimmune conditions, suggesting a common disease etiology.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, other rheumatologic conditions have been reported in patients with HS, such as systemic lupus erythematous. In a 2018 case report (Ben David et al, 2018), a 40-year-old female patient with SLE presented with recurrent abscesses and nodules on the extremities and was ultimately diagnosed with HS. Thus, HS may coexist with other autoimmune conditions, suggesting a common disease etiology.…”
Section: Resultsmentioning
confidence: 99%
“…The connection between HS and other immune‐mediated diseases, such as psoriasis, acne conglobata, pilonidal cysts, pyoderma gangrenosum, alopecia areata, vitiligo and thyroid dysfunction, has been suggested 115,150–152 . Anecdotal reports of HS and systemic lupus erythematosus or interstitial neutrophilic pneumonia exist; yet, this signal is too low‐powered to establish an association 153,154 . Two studies demonstrated a higher frequency of pathogenic MEFV mutations, which is responsible for familial Mediterranean disease, in HS compared with the public 94,155 .…”
Section: Comorbiditiesmentioning
confidence: 99%
“…The pathogenesis of HS is complex, multi-factorial and still poorly understood, with the biological make-up of the individual (especially, genetic polymorphisms, endocrinological drivers and hormones), as well as epigenetic factors and environmental interactions playing a major role [4]. HS is a systemic, autoinflammatory condition [5] since several disorders, including autoimmune/autoinflammatory conditions, have been shown to be associated with HS, like inflammatory bowel disease (IBD) and spondyloarthropathies [6], non-alcoholic fatty liver disease (NAFLD) [7] or neutrophilic interstitial pneumonia [8], among others.…”
Section: Introductionmentioning
confidence: 99%